2017
DOI: 10.1007/s11356-017-0856-7
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein in Hermetia illucens (Linnaeus, 1758) larvae (Diptera: Stratiomyidae), a potential biomarker for organic waste system

Abstract: Black soldier fly, Hermetia illucens (Linnaeus, 1758), is an important economic fly as its larvae can be used for recycling organic waste, such as food waste and manure. H. illucens larvae (BSFL) could uptake Cd from substrates and accumulate it inside bodies, which need to be monitored during waste treatment. Metallothionein (MT) usually serve as biomarker because of its role in metal homeostasis, detoxification, and dose response of heavy metals. Therefore, a MT gene was cloned from H. illucens (HIMT) that e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…These results coincide with those observed by other authors [15,32,63,64]. In contrast, other studies have indicated that there are no differences between feeding insect meals and conventional meals on the growth performance of poultry birds [63,65,66,67]. The percentage of insect feed addition and the replacement of other feed ingredients such as soybean or fish meal with regard to the respective control diet (as well as the individual bird species) has to be considered when comparing these different feeding trials.…”
Section: Resultssupporting
confidence: 92%
“…These results coincide with those observed by other authors [15,32,63,64]. In contrast, other studies have indicated that there are no differences between feeding insect meals and conventional meals on the growth performance of poultry birds [63,65,66,67]. The percentage of insect feed addition and the replacement of other feed ingredients such as soybean or fish meal with regard to the respective control diet (as well as the individual bird species) has to be considered when comparing these different feeding trials.…”
Section: Resultssupporting
confidence: 92%
“…Metallothionein (MT) proteins have a role in metal detoxification and homeostasis (Amiard-Triquet et al, 1998). In a contaminated environment, MT is considered a potential biomarker for heavy metal exposure in insects and other invertebrates (Hensbergen et al, 2000;Wang et al, 2018). MT gene transcription is enhanced by several stimuli, such as heavy metals, heat shock, and other oxidative stresses (Aoki, 2011;Zhang et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This is a critical scientific challenge in the fields of environment, biology, ecology, and so forth. Therefore, seeking a reasonable and friendly way for biodegradable organic waste has been considered as an efficient and sustainable resolution. , Many insects are reported to be capable of biodegrading organic waste. For example, superworms can degrade polystyrene …”
Section: Introductionmentioning
confidence: 99%